PENGARUH SARANA DAN PRASARANA SEKOLAH TERHADAP HASIL BELAJAR PESERTA DIDIK - Rohmawiani Rosalina; Tito Parta Wibowo; Enong Rohayati; Ulfah Wahyu Harzegovina; Yayah Sofiah; Hadi Hapizi (Jurnal Manajemen Pendidikan, 2026)
This study aims to determine the effect of school facilities and infrastructure on students’ learning outcomes at SD Palurahan 1, Kadu Hejo District, Pandeglang Regency. The study employed a quantitative approach using a causal associative method to analyze the relationship between school facilities and infrastructure variables and students’ learning outcomes. The population consisted of all upper-grade students, while the sample included 60 students selected through proportional random sampling techniques. Data collection techniques were carried out through questionnaires to measure school facilities and infrastructure conditions and report card documentation to determine students’ learning outcomes. Data were analyzed using descriptive statistics and simple linear regression with a significance level of 0.05. The results showed that school facilities and infrastructure were categorized as good, and students’ learning outcomes were also categorized as good. Hypothesis testing indicated that school facilities and infrastructure had a positive and significant effect on students’ learning outcomes. The coefficient of determination showed a contribution of approximately 35%, while the remaining percentage was influenced by other factors outside this study. Therefore, school facilities and infrastructure play an important role in improving the quality of students’ learning outcomes.